Comparative analysis of free/combined phytosterols--degradation and differential formation of oxidation products during heating of sunflower seed oil. (1st February 2022) - Xu, Baocheng; You, Sicong; Zhang, Liangxiao; Ma, Fei; Zhang, Qi; Luo, Denglin; Li, Peiwu
Abstract: Sunflower seed oil was subjected to heating under 90, 180, and 220 °C for up to 180 min. A decrease in free phytosterols (FPS) and combined phytosterols (CPS) as well as a concurrent formation of individual free and combined phytosterol oxidation products (POPs) were determined and evaluated. During heating, the FPS decreased and were more susceptible to oxidation (a total of 22.8% of FPS vs. 19.2% of CPS was lost, respectively, after heating at 220 °C for 180 min), while lesser amount of the lost FPS (about 13.0% vs. 45.6%, after heating at 220 °C for 180 min) were transformed into typical oxidation derivatives compared to their corresponding combined forms. The absolute contents of individual POPs derived from FPS and CPS increased with heating temperature and time. We discovered that 7α-OH-, 7β-OH-, 5, 6β-epoxy- and 5, 6α-epoxy-PS derived from CPS were generated faster and at higher levels during heating at 180 °C and 220 °C for 180 min compared to those derived from the corresponding FPS, although the initial content of CPS (695.8 μg/g of oil) were far less than that (1545.5 μg/g of oil) of corresponding FPS. Highlights: The differences in free and combined phytosterols (FPS, CPS) oxidation were elaborated. FPS were more susceptible to oxidation than their combined forms during heating. CPS were more prone to form phytosterol oxidation products than FPS during heating.